(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Background: Surgical site infections causes significant morbidity and mortality of patients and causes more difficult to treat if unexpected cause behind the infection like tuberculosis. Delayed surgical site infection after initial healing are uncomfortable for both surgeons and patient. Methods: Wound tissue from 18 patients with delayed surgical site infection not responding to antibiotics used for pyogenic infection were collected and examined histopathologically. Results: Of the 18 patients, 9 revealed histologically tuberculosis, 7 non-specific chronic inflammation and others showed foreign body granulomma. Association between histopathological report and incidence of tuberculosis is significant (p<0.001) and association between onset of infection and incidence of tuberculosis also significant (p<0.05). Conclusion: A high degree of suspicion is required in case of delayed or recurrent surgical site infection to diagnose tuberculosis as a cause. J Bangladesh Coll Phys Surg 2014; 32: 186-189